Parental Education and Delirium Risk after Surgery in Older Adults. Issue 2 (15th March 2023) - Arias, Franchesca; Chen, Fan; Shiff, Haley; Marcantonio, Edward R.; Jones, Richard N.; Schmitt, Eva M.; Metzger, Eran; Fong, Tamara G.; Travison, Thomas G.; Inouye, Sharon K.
ABSTRACT: Objectives: Efforts to conceptualize risk factors for postoperative delirium in older adults have focused on the time proximate to the episode, but how early-life exposures influence delirium risk is poorly understood. Methods: An observational cohort of 547 patients aged 70+undergoing major non-cardiac surgery at two academic medical centers in Boston. Demographic characteristics, cognition, parental education, health, and participation in cognitively stimulating activities were assessed prior to surgery. Delirium incidence and severity were measured daily during hospitalization. Results: Higher paternal education was associated with significantly lower incidence of delirium ( X 2 (1, N =547)=8.35, p <.001; odds ratio OR=.93, 95% CI, .87 to .98) and inversely associated with delirium severity ( r(545) =−.13, p <.001). Higher maternal education was associated with lower delirium incidence but did not reach statistical significance. The effect of paternal education on delirium incidence was independent of the patient's education, estimated premorbid intelligence, medical comorbidities, neighborhood disadvantage, and participation in cognitively stimulating activities ( X 2 (2, N =547)=31.22, p <.001). Conclusions: Examining early-life exposures may yield unique insights into the risks and pathogenesis of delirium. Clinical Implications: Evaluating long-term factors that increase vulnerability to delirium may improve our ability to calculate risk. It may guide clinical decision-making and inform pre- and post-operative recommendations.